Therapy of asthenic disorders - O. A. Shavlovskaya (Медицинский совет, 2013)
The article reviews several research works on asthenia. There is a classification and diagnostic criteria for asthenia. The prevalence of asthenic conditions, current therapeutic approaches and therapeutic effects are demonstrated. Particular attention is given to the therapy of asthenic disorders with the domestric drug Metaprot. There are results of studies that evaluated anti-asthenic and psychoactivating effect of Metaprot which can be used as metabolic cerebral protection in acute ischemic stroke; in the treatment of craniocerebral injury; treatment of patients with encephalopathy; multimodal treatment and rehabilitation of patients with hepatitis A; treatment of patients with chronic nonspecific respiratory diseases and ischemic heart disease. The experience of Metaprot use as part of multimodal therapy in the recovery phase of acute radiation syndrome is described.